Análise estrutural em relictos de cerrado no parque estadual do Guartelá, município de Tibagi, estado do Paraná, Brasil - Carmo, Marta Regina Barrotto do (2012)
This study was accomplished in existing Cerrado's relicts at State Park Guartelá, Tibagi, PR (24°39'10S and 50°15'25W), which represent one of the last extreme-meridional remanescents of this type of formation. Fifty plots with dimensions of 5x5m were allocated for phyto-sociological analysis, including in the sample individuals with height ≥ 1 m, divided into two samples to evaluate the following strata: a) upper-plants with DAS ≥ 3 cm, and b) intermediate - plants with DAS <3cm. Moreover, in each plot, there were established sub-plots with dimensions of 1x1m for sampling the lower stratum, comprised by individuals with height <1m and >10cm. The complete survey found 1340 individuals distributed in 28 families, 66 genera and 115 species. The diversity index was higher for the mean component (H'=3.30), followed by the superior component (H'=3.09) and the inferior (H'=2.91). The frequent occurrence of bushes is a remarkable characteristic of the physiognomy of the areas inside the park and 82 % of the populations studied are distributed in aggregated standard. Because it is a marginal region of occurrence of cerrado vegetation, now under the influence of a subtropical climate, more humid and cold, compared to the core area of this biome, it is noted that these areas are characterized by a decrease in stature, richness and diversity of its flora. Nevertheless, they preserve typical species of the Brazilian Savannah; but, due to their distribution in relicts and been, in part, devastated, some are included in the red list of endangered plants in Parana state, which evidences the importance of conservation and management of these areas.